Improving the detection and management of common non-communicable diseases in adults in rural Sidama National Regional State, Ethiopia: Study protocol - Melaku Haile Likka; Hiwot Abera Areru; Betelihem Eshetu Birhanu; Desalegn Tsegaw Hibistu; Bernt Lindtjørn (PLoS ONE, 2026)
Background The World Health Organization (WHO) has designed a package of essential non-communicable disease (PEN) strategies to improve the detection and management of non-communicable diseases. However, the implementation of the PEN in rural health facilities in Sidama National Regional State is at an early stage, and the readiness of rural primary healthcare units (PHCUs) to implement the strategy is unknown. We, therefore, propose to apply the strategy in the catchment areas of Dobe-Toga Health Center, a rural PHCU in Sidama National Regional State, Ethiopia, and improve non-communicable diseases care among adults aged ≥45 years. Aim We primarily aim to evaluate the effectiveness of a WHO PEN-based care model, which we will implement in a rural setting, in controlling blood pressure and glucose levels among older adults. It will also determine the prevalence of undiagnosed hypertension, pre-diabetes, and diabetes. Additionally, the study seeks to assess the readiness of rural PHCUs to implement the WHO PEN approach and examine the relationship between NCD diagnoses and community-based health insurance (CBHI) membership. Methods The study will be conducted in the catchment areas of Dobe-Toga Health Center from April 2024 to February 2025 and includes multiple components. One component is a cross-sectional readiness assessment of PHCUs in Sidama National Regional State, which will be undertaken involving 41 health centers and 4 primary hospitals, triangulated by qualitative data collection. The remaining study components will be conducted exclusively in the catchment areas of Dobe-Toga Health Center in two phases. In Phase 1, cross-sectional surveys will be conducted to determine the prevalence of undiagnosed hypertension, type 2 diabetes mellitus, and pre-diabetes in a randomly selected sample of 3,301 older adults. Additionally, the participants’ willingness to pay (WTP) for HbA1c tests will be assessed, and CBHI-related surveys will be conducted. In Phase 2, the individuals diagnosed with these conditions will be linked to the health center and enrolled in a WHO PEN–based care model. The effects of the care model in controlling blood pressure and glucose will be examined. Furthermore, the participants’ adherence to self-care practices will be determined.